2017
DOI: 10.1002/lary.26794
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the endoscopic modified Lothrop procedure: A systematic review and meta‐analysis

Abstract: In the last decade, EMLP has been performed more frequently for tumors. Recent studies have demonstrated improved symptom outcomes and a trend toward improved patency rates. The revision rate increased significantly when follow-up exceeded 2 years. Laryngoscope, 128:317-326, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 47 publications
(96 reference statements)
2
28
0
1
Order By: Relevance
“…Our total revision rate in the whole cohort was 4% (2 of 50), for a mean follow‐up period of 2.9 years, which is comparable with findings from earlier studies . Of note, the revision rate was higher in the control group (8.7%, 2 of 23) than in the mucosal grafts and flaps group (0%, 0 of 27).…”
Section: Discussionsupporting
confidence: 88%
“…Our total revision rate in the whole cohort was 4% (2 of 50), for a mean follow‐up period of 2.9 years, which is comparable with findings from earlier studies . Of note, the revision rate was higher in the control group (8.7%, 2 of 23) than in the mucosal grafts and flaps group (0%, 0 of 27).…”
Section: Discussionsupporting
confidence: 88%
“…In our Draf 3 cohort, 86.7% of patients at last follow‐up showed improved SNOT‐22 scores greater than the MCID, while a recently published systematic review on Draf 3 outcomes reported significant symptom improvement in 86.5% of patients. In our series, 88.2% had patent neo‐ostia and 11.8% required revision surgery; similarly, the same systematic review showed patent neo‐ostia in 90.7% of patients and a 12.6% revision rate . While no systematic review of the Draf 2B procedure exists to our knowledge, the results of our Draf 2B cohort appear similar to previously published case series …”
Section: Discussionsupporting
confidence: 89%
“…It is important to acknowledge that we excluded patients with more severe comorbidities, for which the Draf 3 procedure has been more commonly utilized than the Draf 2B . Because the Draf 3 procedure results in a wider, interconnected frontal cavity with enhanced medial and lateral frontal sinus access, there may be surgical indications for which the Draf 3 may be preferable, such as ciliary dyskinesia or tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Con el desarrollo de la cirugía endoscópica nasal, las aplicaciones del Draf III se han ampliado. Actualmente incluyen la resección de diversos tipos de tumores del seno frontal, cierre de fístulas de líquido cefalorraquídeo, manejo de fracturas del seno frontal y como parte de abordajes endonasales extendidos a la fosa craneal anterior, entre otras 3 .…”
Section: Introductionunclassified